Literary Expression in Post-Apartheid South Africa (2014)
Literary productivity in South Africa increased dramatically with the political change from apartheid to multi-racial democracy in 1994. This surge has attracted much interest, with critics trying to map the changes observable on the post-apartheid literary landscape using race and gender. However, adequate attention has not been given to the emergent literature from the political perspective. This study, therefore, examined new themes and forms in selected post-apartheid literature in order to show the impact of political change on literary expression. The study adopted Jean-Francois Lyotard‟s and Homi Bhabha‟s models of postmodernism and postcolonialism respectively. It selected five texts, based on thematic affinities, from each of the genres of prose, drama and poetry. The prose texts are End, A Duty of Memory, The Quiet Violence of Dreams (TQVD), Thirteen Cents and Disgrace. The drama texts are Nothing but the Truth (NBTT), Ubu and the Truth Commission (Ubu), Dream of the Dog (DOD), Molora and Reach! while those from poetry are Dancing in the Rain (DITR), Handsome Jita (HJ), It All Begins, Letter to the State and The New Century of South African Poetry. The methods of analysis are literary and critical interpretations of the texts. Inscriptions of sexual acts, non-normative sexuality and open inter-racial romance, politically forbidden before 1994, are prominent thematic concerns in the novels. Linguistic vulgarism and eroticism are inscribed brazenly in End, TQVD and Thirteen Cents. Postmodern inter-textuality also inscribes eroticism in End. A Duty of Memory and Disgrace explore gay relations only between women, but with restraint. In TQVD and Thirteen Cents, characterisation establishes the inter-racial dimension of gay relations. Specific spatial settings in End and Thirteen Cents destroy the myth of secrecy about the sexual act. The drama texts thematise national reconciliation. However, while Ubu and DOD dwell on the significance of truth in reconciliation, NBTT and Reach! emphasise memory. Molora advocates forgiveness. Using „faction‟, Ubu, NBTT and Molora directly appropriate materials from South Africa‟s politically-motivated Truth and Reconciliation Commission while DOD and Reach! Do so indirectly. While characterisation is fictional in the plays, some of the spatial and temporal settings are real. In poetry, the theme of disillusionment about the hopes which multi-racial democracy had held for the people is depicted. This is done directly in all the collections, but also ironically and satirically in It All Begins, Dancing in the Rain, Handsome Jita and Letter to the State. Proverbs and wise sayings, as well as combinations of standard codes and slang, feature noticeably in DITR, HJ and It All Begins. In all the genres, postcolonial hybridity such as glossing, abrogation and linguistic pluralism features. The multiplicity of thematic preoccupations and executions in post-apartheid South African literature illustrates how political change affects the country‟s literary expression. This multiplicity, occasioned by the new political realities, defines the new trajectory of South African literature